Elas, outras, algumas - Pereira, Renata Felisatti Gonçalves (2021)
This research was done by a woman film editor. This is a thought of montage/editing (process) that seeks to bring out women’s voice, the women film editors and women storytellers through images and sounds. The women, throughout the history and the history of cinema/films, have been erased and their stories never told. This research explains a way of thinking, of making films through the stories of some women and the creation of characters who lend their voices and bodies to tell part of this story, so that the voice is always of a woman and her process and relations